1986
DOI: 10.1017/s0043174500067114
|View full text |Cite
|
Sign up to set email alerts
|

Weed Control in Irrigated Seedling Alfalfa (Medicago sativa)

Abstract: Spring-applied herbicides were evaluated in the field in 1982 through 1984 in western Nebraska for selective weed control in irrigated seedling alfalfa (Medicago sativaL. ‘Appollo’). Weed densities were least in plots treated preplant with benefin [N-butyl-N-ethyl-2,6-dinitro-4-(trifluoromethyl)benzenamine] in combination with postemergence applications of 2,4-DB [4-(2,4-dichlorophenoxy) butyric acid]. Combinations of sethoxydim {2-[1-(ethoxyimino)butyl]-5-[2-(ethylthio)propyl]-3-hydroxy-2-cyclohexen-1-one} wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
3
9
0
Order By: Relevance
“…All herbicides provided >96% control of the annual broadleaf weeds evaluated in this research. These data are in agreement with other studies that have reported excellent annual broadleaf weed control with each of these herbicide treatments in alfalfa (Fawcett and Harvey, 1978; Johnson et al, 2001; McCordick et al, 2008; Wilson, 1986).…”
Section: Resultssupporting
confidence: 92%
“…All herbicides provided >96% control of the annual broadleaf weeds evaluated in this research. These data are in agreement with other studies that have reported excellent annual broadleaf weed control with each of these herbicide treatments in alfalfa (Fawcett and Harvey, 1978; Johnson et al, 2001; McCordick et al, 2008; Wilson, 1986).…”
Section: Resultssupporting
confidence: 92%
“…Research has shown that postemergence application of chlorsulfuron can injure seedling as well as estab lished alfalfa (6) and its residues in the soil can inhibit nodulation and growth of alfalfa (7). Injury to alfalfa from 2,4-D, glyphosate, and bromoxynil was reported when these herbicides were applied at relatively high rates (3,4,6,11,12). However, the response of alfalfa to these and sulfonylurea herbicides as might occur from herbicide drift has not been documented.…”
Section: Herbicide Drift Can Injure Plants Considerable Dis Tance Dowmentioning
confidence: 99%
“…When imazethapyr rate was increased to 140 glha the addition ofUAN to the spray solution increased all legume injury. Legume density was not reduced by POST applications of imazethapyt Cicer milkvetch and yellow sweetclover density 20 OAT increased with POST application of imazethapyr, probably the result of weed control which has previously been shown to enhance legume establishment (15).…”
Section: Resultsmentioning
confidence: 84%
“…\\eeds pose a major production problem in legumes where they compete for water, nutrients, and light and reduce forage quality. \\eeds in new alfalfa seedings can decrease legume stands (15). As weeds increase, the alfalfa percentage in forage declines (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation